Peer rejection and internet gaming disorder: the mediating role of relative deprivation and the moderating role of grit - Li, Jingjing; Wei, Chang; Lu, Jiachen (Frontiers in Psychology, 2025)
Background Internet Gaming Disorder (IGD) is a new behavioral addiction. A large number of empirical studies have shown that Internet Gaming Disorder has a high level of comorbidity with other diseases, including depression, anxiety, obesity, internalizing and externalizing behavioral problems, however, little is known about the mediating and moderating mechanisms underlying this relation. The current study adopted a three-time longitudinal study investing the mediating effect of relative deprivation on the association between peer rejection and IGD, and whether this mediating effect was moderated by the grit. Methods A total of 1,065 students in China anonymously completed three-time longitudinal study questionnaires. The average age was 10.19 years (SD = 0.75) and the interval between measurements was 6 months.PROCESS for SPSS proposed by Hayes was used to test a moderated mediation model, with gender, age as covariates. Results T1 peer rejection positively predicted T3 Internet Gaming Disorder. Relative deprivation at T2 plays a complete mediating role between peer rejection at T1 and Internet gaming disorder at T3. At the same time, it was found that the personality trait of T3 grit plays a moderating role in the relationship between T2 relative deprivation and T3 Internet gaming disorder. This suggests that peer rejection is an important predictor of Internet Gaming Disorder, and that individuals with high levels of grit are less likely to become addicted to Internet games even if they experience relative deprivation. Limitations Measures of study variables were self-reported. Affected by factors such as social desirability, the research results may be biased. Conclusion These findings emphasize relative deprivation as a potential mechanism linking peer rejection IGD. Grit was an important protective factor to weaken this indirect effect. Intervention programs aimed at reducing IGD may benefit from the current research.